Robin Hood - Bedford, Brian 1935-; Reitherman, Wolfgang 1909-1985; Buena Vista Home Entertainment (Firm); Walt Disney Home Entertainment (Firm) (Burbank, CA Walt Disney Home Entertainment Distributed by Buena Vista Home Entertainment, 2006)
The animal kingdom serves up a feast of bowmanship, swordplay, and daring deeds. England is at war and ruled by a phony king! Greedy Prince John and his slithering sidekick, Sir Hiss, are taxing Nottingham's residents to the limit
Originally released as a motion picture in 1973
1
Keywords: Avarice -- Juvenile drama; Robin Hood (Legendary character) -- Juvenile drama; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs